Price stability of agricultural products in the European Union - Spasojević Boris; Đukić Aleksandar; Erić Ognjen (Ekonomika Poljoprivrede (1979), 2018)
Agricultural sector in the EU functions under strong influence of the CAP. EU finances the measures to support production of agricultural products and food. CAP is founded on the goals of ensuring price stability. Correlation and regression analysis have largely confirmed the given hypotheses. General price levels in EU, as well as the prices of agricultural products have been stable, as shown by the respective trend line equations. Correlation and regression analysis of support for agricultural production and prices of agricultural products indicate a moderate correlation level, i.e. the support contributes to price stability. Correlation analysis confirms the influence of prices of industrial products on the prices of agricultural products. Results of price movement analysis of agricultural products and foods on one hand, and independent variables affecting prices on the other, show that CAP objectives have been mainly accomplished. Thus, interventionism in agriculture brings economic effects and justifies the CAP measures.